Articulating addiction in alcohol and other drug policy: A multiverse of habits - Fraser, Suzanne (2015)
Concepts of addiction differ across time and place. This article is based on an international research project currently exploring this variation and change in concepts of addiction, in particular in the field of alcohol and other drug (AOD) use. Taking AOD policy in Australia and Canada as its empirical focus, and in-depth interviews with policy makers, service providers and advocates in each country as its key method (N = 60), the article compares the addiction concepts articulated by professionals working in each setting. Drawing on Bruno Latour's theoretical work on the body and his proposal for a better science based on the 'articulation of differences', it explores the accounts of addiction offered across the Australian and Canadian project sites, identifying a shared dynamic in all: the juggling of difference and unity in discussions of the nature of addiction, its composite parts and how best to respond to it. The article maps two simultaneous trajectories in the data - one moving towards difference in participants' insistence on the multitude and diversity of factors that make up addiction problems and solutions, and the other towards unity in their tendency to return to narrow disease models of addiction in uncomfortable, sometimes dissonant, strategic choices. As I will argue, the AOD professionals interviewed for my project operate in two modes treated as distinct in Latour's proposal: in turning to reifying disease labels of addiction they take for granted, and work within, a 'universe of essences', but in articulating the multiplicity and diversity of addiction, they grope towards a vision of a 'multiverse of habits'. The article concludes by addressing this tension directly, scrutinising its practical implications for the development of policy and delivery of services in the future, asking how new thinking, and therefore new opportunities, might be allowed to emerge.